New assay of protective activity of Rocky Mountain spotted fever vaccines. - Anacker, R L (1976)
Areas under the fever curves of guinea pigs inoculated with Rocky Mountain spotted fever vaccine over a restricted dose range and infected with a standardized dose of Rickettsia rickettsii varied linearly with log10 dose of vaccine. A calculator was programmed to plot fever curves and calculate the vaccine dose that reduced the fever of infected animals by 50%.